Teachers’ Creative Behaviors in STEAM Activities With Modular Robotics - Leroy, Anaïs; Romero, Margarida (Frontiers in Education, 2021)
As STEAM activities require both the teachers and learners to be creative, it is important to train teachers to instruct and guide creativity not only when students begin a task, but also throughout its entire process to persistently maintain creative behaviors. To assess the creative process in teacher education, a currently limited topic within the literature, we examined 37 in-service teachers, who were participating in a creative pedagogy course, through a divergent creativity test (Alternative Uses Test) and a CreaCube task (a creative problem-solving task involving modular robotics). We used CreaCube as a digital manipulative task that was performed twice to ensure the creative assessment’s authenticity in relation to STEAM education. In the second execution, the participants did not know whether they had to reproduce the same solution or find a new one. Our results show that only a quarter of the teachers proposed new solutions during the task repetition, and that this conservative and repetitive behavior increased the task completion speed. However, this suggests that even in the context of creative pedagogy courses, teachers’ tendencies to prioritize speed and the application of existing solutions remains a barrier to engaging in more creative behaviors that require inhibiting previous solutions and exploring new ideas. This study sheds light on the importance of teachers experimenting with this conservative behavior bias during their training and the significance of persistently applying creative behaviors in STEAM activities. Accordingly, it is essential that teachers consider these factors when developing and delivering their courses.